2020
DOI: 10.1038/s41598-020-71880-4
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical composition and potentially toxic elements in the Kyrgyzstan portion of the transboundary Chu-Talas river basin, Central Asia

Abstract: Water chemistry and the assessment of health risks of potentially toxic elements have important research significance for water resource utilization and human health. However, not enough attention has been paid to the study of surface water environments in many parts of Central Asia. Sixty water samples were collected from the transboundary river basin of Chu-Talas during periods of high and low river flow, and the hydrochemical composition, including major ions and potentially toxic elements (Zn, Pb, Cu, Cr, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…The charge balance error percentage (CBE) [36] was between 0.4 and 4.5, which is less than ±5%. After the water samples were filtered through a 0.45 µm microporous membrane, 200 mL was acidified with a 0.6 mL nitric acid solution (volume ratio 1:1), and the As content in the solution was analyzed with an Agilent 8800 inductively coupled plasma mass spectrometer (Agilent Technologies, Santa Clara, CA, USA) [7,37].…”
Section: Sample Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The charge balance error percentage (CBE) [36] was between 0.4 and 4.5, which is less than ±5%. After the water samples were filtered through a 0.45 µm microporous membrane, 200 mL was acidified with a 0.6 mL nitric acid solution (volume ratio 1:1), and the As content in the solution was analyzed with an Agilent 8800 inductively coupled plasma mass spectrometer (Agilent Technologies, Santa Clara, CA, USA) [7,37].…”
Section: Sample Collection and Analysismentioning
confidence: 99%
“…The river becomes the link between the mountain system and the oasis system and is the foundation for ecological construction and economic development in arid areas. The composition of major ions in river water is one of the most important indicators of river water quality and contains important environmental information on things, such as climate, bedrock type, and human activity in the watershed [7], and it is the most basic indicator for irrigation evaluation and drinking-water-safety evaluation [8,9]. In recent years, scholars have paid much attention to the water-resource and environmental problems in the western part of the Tianshan [10,11] and Altay [12,13] Mountains (Mts.…”
Section: Introductionmentioning
confidence: 99%
“…At present, some scholars have analyzed the arsenic or fluoride concentrations in some rivers of Kyrgyzstan, such as the Shu River, Shor-Koo River, and Aksu River (Solodukhin et al 2016), surface water in Mailuu Suu town (Alvarado et al 2014;Aparin et al 2012) and the Naryn River (Ma et al 2019). Simultaneously, some scholars have conducted human health risk assessments for potential toxic elements in the rivers of Kyrgyzstan and have found that the arsenic levels in the rivers of the Issyk-Kul Basin (Liu et al 2020) and the transboundary river of the Chu-Talas River in Kyrgyzstan (Ma et al 2020) were harmful to human health. However, most of the research objects were limited to a single river, watershed or area.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, some scholars have conducted human health risk assessments for potential toxic elements in the rivers of Kyrgyzstan and have found that the arsenic levels in the rivers of the Issyk−Kul Basin 17 and the transboundary river of the Chu-Talas River in Kyrgyzstan 18 were harmful to human health. However, the above research objects were generally limited to a single river, watershed or prefecture, and the concentrations and distributions of fluorine and arsenic in the rivers of Kyrgyzstan, spatiotemporal distribution characteristics of fluorine and arsenic in river water, influencing factors of spatial distributions of fluorine and arsenic in river waters, whether fluorine and arsenic simultaneously exceeded the established limits, and the health risk of both to human health are still unclear.…”
Section: Introductionmentioning
confidence: 99%